أثر الأزمة السورية على الأمن السياحي في سورية (دراسة مقارنة بين فترة الأزمة وما قبلها 2007-2013) - صقر, محمد; سلمان, حيان; عباس, لورا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول البحث أهمية صناعة السياحة الآمنة كونها تشكل الركيزة الأساسية في تطوير صناعة السياحة في ظل تيسير سبل السفر والاتصال والحركة والانتقال , وفي ظل امتلاك سورية المقومات الأساسية للسياحة, وغيرها من مقومات الجذب السياحي.ومع ذلك يظل الجانب الأهم للحفاظ على هذه المقومات السياحية الأمن بشكل عام والأمن السياحي بشكل خاص, حيث يعتبر أمن وسلامة السياح في المرافق والأنشطة السياحية والأثرية وأمن وسلامة المرافق والأنشطة السياحية والأثرية من العناصر الأساسية في تنمية وتطوير قطاع السياحة, خاصة في ظل الأعمال الإرهابية التي أصبحت تشكل خطراً على مستقبل السياحة وحياة الناس.وهذا يتطلب إيجاد استراتيجية للسياحة تعتمد على جوانب الجذب السياحي : توفر الأمن – توفير الخدمات السياحية– الطبيعة الخلابة – وسائل الإعلام – المعارض - أنشطة سياحية أخرى . ويتطلب أيضاً وجود إدارات لقطاع الأمن السياحي في ظل تنامي الحركة السياحية والتوسع في مقومات وعناصر النشاط السياحي .This research is about the importance of safe of tourism industry becausa. It constitutes the center Piece in the development of tourism industry under the development of tourism industry under the facilitation of travel, communications, movement, and transporting in the shadow of the basic components of tourism and other elements of tourist attractions.However, the most important aspects to keep these tourism resources are Security in general and tourism Security. In particular, where the safety and Security of tourists in the tourist Amenities and activities and archaeological sites, and the Security of the tourist amenities and activities and archaeological sites are essential elements in the development of the tourism Sector, especially in light of the terrorist acts that have become athreat to the future of tourism and People's lives.This requires a tourism strategy based on aspects of the tourist attractions: providing security, tourist services, charming nature, media, exhibitions and other tourist activities.This also requires the Presence of the department of the security sector of tourism in light of the growing tourist traffic and the expansion of the components and the elements of the tourism activity.